The Symbolism of Double Consciousness in the Works of W.E.B. Du Bois and its Evolution in Contemporary Black Literature - S, Neethu (International Journal of Environment, Agriculture and Biotechnology, 2023)
This research paper traverse into the concept of double consciousness as presented by W.E.B. Du Bois in his seminal work The Souls of Black Folk and explores how this theme has been redefined and adapted in contemporary black literature. The study examines the symbolic use of double consciousness in characters, narratives, and motifs, tracing its evolution as a literary device and its continued relevance in the portrayal of black identity and experience. Through an in-depth analysis of selected works spanning different periods, the research aims to shed light on the ways in which black writers have engaged with and transformed this concept to reflect the complexities of black life in diverse sociocultural contexts.